A Concordance to the Poems of W.B. Yeats - Parrish, Stephen Maxfield (Cornell University Press, 2019)
Now it is possible for the first time to trace in a systematic way the language patterns of one of the greatest poets who have written in English, W. B. Yeats.Like A Concordance to the Poems of Matthew Arnold, the first of the Cornell Concordances that are under the general editorship of Professor Parrish, this volume was produced on an IBM 704 electronic data-processing machine. Computer technique has so advanced that the Yeats concordance includes punctuation and gives cross references for the second parts of hyphenated words. The frequency of every word in Yeats's poems is given, and an appendix lists all indexed words in order of frequency. The body of this book consists of an index of all significant words in Yeats, each word listed in the line or lines in which it occurs. The concordance is based on the variorum text of Yeats, edited by Alspach and Allt, and includes all variants that occur in printed versions of Yeats's poems.